2020
DOI: 10.3390/polym12061309
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Melt-Mixed 3D Hierarchical Graphene/Polypropylene Nanocomposites

Abstract: The mechanical properties of novel low percolation melt-mixed 3D hierarchical graphene/polypropylene nanocomposites are analyzed in this study. The analysis spans a broad range of techniques and time scales, from impact to tensile, dynamic mechanical behavior, and creep. The applicability of the time–temperature superposition principle and its limitations in the construction of the master curve for the isotactic polypropylene (iPP)-based graphene nanocomposites has been verified and presented. The Williams–Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…This solid‐like behavior of the CPCs suggests that a percolated network structure was formed and indicates a good dispersion and/or distribution of the CB conductive filler particles/agglomerates inside the polymer matrix. [ 52 ] Similar behavior was described by Hassanabadi et al [ 49 ] in the case of carbon nanotube‐reinforced EVA or by Wu and Zheng [ 53 ] in the case of HDPE/CB composites. Pötschke et al [ 50 ] concluded that the changes in the storage modulus are related to the formation of a conductive network in which, in rheology, the filler particles need to touch each other, contrary to the case of the electrical percolation.…”
Section: Resultssupporting
confidence: 70%
“…This solid‐like behavior of the CPCs suggests that a percolated network structure was formed and indicates a good dispersion and/or distribution of the CB conductive filler particles/agglomerates inside the polymer matrix. [ 52 ] Similar behavior was described by Hassanabadi et al [ 49 ] in the case of carbon nanotube‐reinforced EVA or by Wu and Zheng [ 53 ] in the case of HDPE/CB composites. Pötschke et al [ 50 ] concluded that the changes in the storage modulus are related to the formation of a conductive network in which, in rheology, the filler particles need to touch each other, contrary to the case of the electrical percolation.…”
Section: Resultssupporting
confidence: 70%
“…The second one was α c relaxation process associated with relaxations arising from the crystalline phases of the polymer matrix. 59…”
Section: Resultsmentioning
confidence: 99%
“…The second one was a c relaxation process associated with relaxations arising from the crystalline phases of the polymer matrix. 59 Table 6 shows data of E', E'', T g , E"/E' ratio and T a* of PP and nanocomposites. PP/ZrP system did not show tendency concerning the screw speed.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…The selected solvent must be compatible with the polymer resin and be volatile to facilitate the evaporation or distillation processes [ 105 , 108 ]. A wide range of polymers including epoxy [ 109 ], polyvinyl alcohol (PVA) [ 110 ], polyvinyl fluoride (PVF) [ 111 , 112 ], polyethylene (PE) [ 113 , 114 ], polypropylene [ 115 , 116 ], polymethylmethacrylate (PMMA) [ 117 , 118 ], polyurethane (PU) [ 119 , 120 ], polystyrene (PS) [ 121 , 122 ] have been explored and found to be suitable for graphene/polymer composite manufacturing via the solution mixing technique. Consequently, polymer resin can intercalate between the graphite layers more easily during the composite fabrication process, thus, resulting in a uniform distribution of graphene or modified graphene materials in the polymer resin [ 123 ].…”
Section: Production Process Of Graphene-based Materialsmentioning
confidence: 99%